2022
DOI: 10.21873/anticanres.15907
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Multi-gene Panel myRisk in Japan

Abstract: Background/Aim: Hereditary tumors are estimated to account for approximately 5-10% of all tumors. In Europe and the United States, multi-gene panel testing (MGPT) is the standard method used for identifying potential causative genes. However, MGPT it is still not widely used in Japan. The aim of this study was to assess the risk of hereditary tumors in Japanese cancer patients using germline MGPT and provide an overview of MGPT in the Japanese medical system. Patients and Methods: We used the myRiskTM, a 35-ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…Interestingly, our cohort's families who underwent cascade testing had a 54.8% positive rate, which is comparable to the high rates from India: 74% [22]. Other studies have reported Asian ethnicity, along with the high cost of the genetic testing panel, late presentation, unavailability of genetic counsellors and inadequate access in LMICs to be responsible factors [23][24][25].…”
Section: Discussionsupporting
confidence: 71%
“…Interestingly, our cohort's families who underwent cascade testing had a 54.8% positive rate, which is comparable to the high rates from India: 74% [22]. Other studies have reported Asian ethnicity, along with the high cost of the genetic testing panel, late presentation, unavailability of genetic counsellors and inadequate access in LMICs to be responsible factors [23][24][25].…”
Section: Discussionsupporting
confidence: 71%